PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KEPALA BERNOMOR UNTUK MENINGKATKAN HASIL BELAJAR METEMATIKA SISWA PADA MATERI BILANGAN PECAHAN DI KELAS VII MTs MUHAMMADIYAH DURI - Kaffah, Muhammad Silmi Kaffah Silmi; ', Zuhri; ', Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to improve the learning process and improve learning outcomes class VII learners of MTs Muhammadiyah Duri by applying cooperative learning numbered heads model. The subjects were learners in class VII which consisted of 8 women and 8 men with heterogeneous academic ability. This research is a class act with two cycles . Each cycle has four stage : planning , implementation , observation and reflection . Data collection instrument in this study is the observation sheet activities teachers and learners , as well as the achievement test. Sheets were analyzed qualitatively descriptive narrative, while the achievement test were analyzed by descriptive statistical study by analyzing the development of the individual and group values â€‹â€‹, KKM achievement analysis , and analysis of the success of the action. Results of research on the observation sheet shows the activity of teachers and learners have done well and according to plan after the action . Improvements in the learning process of students and increase the number of learners who achieve KKM at the end of each cycle UH compared to the number of learners who achieve a score of KKM on base score. At the base score only 31% of learners who reach KKM , the UH I increased to 63% and the UH II also increased to 81% . The results of this study indicate that the application of cooperative learning numbered heads model can improve the learning process and improve learning outcomes class VII learners of MTs Muhammadiyah Duri in the first semester of the academic year 2013/2014 . Â Keywords: Mathematics Learning Outcomes, Cooperative Learning, Numbered Heads, Classroom Action Research .